Lung ILC2s are activated in BALB/c mice born to immunized mothers despite complete protection against respiratory syncytial virus - Kosanovich, Jessica L.; Eichinger, Katherine M.; Lipp, Madeline A.; Gidwani, Sonal V.; Brahmbhatt, Devarshi; Yondola, Mark A.; Chi, David H.; Perkins, Timothy N.; Empey, Kerry M. (Frontiers in Immunology, 2024)
Activated lung ILC2s produce large quantities of IL-5 and IL-13 that contribute to eosinophilic inflammation and mucus production following respiratory syncytial virus infection (RSV). The current understanding of ILC2 activation during RSV infection, is that ILC2s are activated by alarmins, including IL-33, released from airway epithelial cells in response to viral-mediated damage. Thus, high levels of RSV neutralizing maternal antibody generated from maternal immunization would be expected to reduce IL-33 production and mitigate ILC2 activation. Here we report that lung ILC2s from mice born to RSV-immunized dams become activated despite undetectable RSV replication. We also report, for the first time, expression of activating and inhibitory Fcgamma receptors on ILC2s that are differentially expressed in offspring born to immunized versus unimmunized dams. Alternatively, ex vivo IL-33-mediated activation of ILC2s was mitigated following the addition of antibody: antigen immune complexes. Further studies are needed to confirm the role of Fcgamma receptor ligation by immune complexes as an alternative mechanism of ILC2 regulation in RSV-associated eosinophilic lung inflammation.